Initiating The Integrated Cash Waqf Model Among OIC Countries: Waqf - Ahlis Fatoni (International Journal of Waqf, 2021)
Waqf is a very valuable asset in the development of human’s social life. Its role in wealth distribution and poverty alleviation are the target that to be achieved by waqf. To achieve this role, the government has created several real productive waqf innovation programs, for instance cash waqf linked sukuk, insurance waqf, waqf-based palm factory, waqf-based office towers and insurance policies. This study aims to initiate the integrated cash waqf model among OIC countries and to know the development trend of waqf model research published by leading journals on Islamic economics. The data analyzed consisted of 118 indexed research publications. The data is then processed and analyzed using the VoS viewer application to find out the bibliometric map of the waqf model research development. Lastly, we would like to provide an offering in developing cash waqf model among OIC country members.